Synergistic effect of dopant combination and switchover in formation mechanism of polyaniline nanowire. Issue 8 (31st October 2014) - Bhandari, Subhendu; Khastgir, Dipak
ABSTRACT Self‐assembled polyaniline (PAni) was synthesized electrochemically in dimethylformamide medium to study the effect of simultaneous use of organic–inorganic dopant combination in aprotic polar synthesis medium. During the synthesis process, simultaneous dual doping was performed using p‐toluenesulfonic acid and sulfuric acid with varying the ratio of the dopants keeping their total concentration unchanged. Nanowire meshes were formed where switchover in nanostructure formation is observed. Nanowire in individually doped PAni was formed with directional joining of smaller nanoparticles or from multilayered tubular nanostructures whereas, for dual doped PAni, either of these two was observed. Periodicity parallel and perpendicular to polymer chain were found in well correlation with diameter of nanowires. Synergistic improvements in AC conductivity, specific capacitance, and thermal degradation within certain temperature range were observed in particular ratio of the dopants. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41520.